Geological structure and kinematics of normal faults in the Otway Basin, Australia, based on quantitative analysis of 3‐D seismic reflection data. (7th August 2015) - Ziesch, Jennifer; Aruffo, Chiara M.; Tanner, David C.; Beilecke, Thies; Dance, Tess; Henk, Andreas; Weber, Bastian; Tenthorey, Eric; Lippmann, Andrea; Krawczyk, Charlotte M.
Abstract: The Otway Basin in the south of Victoria, Australia underwent three phases of deformation during breakup of the southern Australian margin. We assess the geometry and kinematics of faulting in the basin by analysing a 3‐D reflection seismic volume. Eight stratigraphic horizons and 24 SW‐dipping normal faults as well as subordinate antithetic faults were interpreted. This resulted in a high‐resolution geological 3‐D model ( ca . 8 km × 7 km × 4 km depth) that we present as a supplementary 3‐D PDF (Data S1). We identified hard‐ and soft‐linking fault connections over the entire area, such as antithetic faults and relay ramps, respectively. Most major faults were continuously active from Early to Late Cretaceous, with two faults in the northern part of the study area active until at least the Oligocene. Allan maps of faults show tectonic activity continuously waned over this time period. Isopach maps of stratigraphic volumes quantify the amount of syn‐sedimentary movement that is characteristic of passive margins, such as the Otway Basin. We show that the faults possess strong corrugations (with amplitudes above the seismic resolution), which we illustrated by novel techniques, such as cylindricity and curvature. We argue that the corrugations are produced by sutures between sub‐vertical fault segments and this morphology was maintained during fault growth. Thus, they can be used to indicate the kinematics vector of the fault movement. This evidences, together with left‐stepping relay ramps, that 40% of the faults had a small component (up to 25°) of dextral oblique slip as well as normal (dip‐slip) movement.